Exploring the Potential and Constraints of Smallholder Aquaculture in Marginalized Saline Areas in Pakistan - Rossignoli, Cristiano; Obi, Chinedu; Ali, Syed (WASAPC, 2022)
Aquaculture is still a relatively young activity in Pakistan, but there is immense potential for the sector to develop. Aquaculture has been identified as an alternative livelihood source for many rural farming households living in areas with brackish groundwater. Due to the arid and semi-arid climate of Pakistan, which results in scarce and irregular rainfall, several rural areas are affected by salinity and waterlogging. It is estimated that more than 6 million hectares of Pakistani soil are affected by salinity. Salinity in the soil has caused many lands to be unsuitable for growing crops, and thousands of hectares have been abandoned. As an alternative livelihood, aquaculture can be adopted on such saline lands that are not suitable for crop cultivation. However, there is still limited research and understanding of the constraints and development opportunities for small-holder saline aquaculture farmers in marginalized saline areas of Pakistan. Abstract accepted and presented at WAS2022 – published in the book of abstracts at pag 605.